Development of Printed Module of Plants Structure Materials and Its Technology-Based Utilization on The Eighth-Grade Cross Puzzles at Smp Negeri 35 Pekanbaru - Agprianti, Nurul; Agusminarti, Agusminarti; Sholihat, Neng (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2022)
This research aims to create teaching materials for plant tissue structure materials in the form of printed scientific modules for use in class VIII crossword-based technology. The research model used is the ADDIE research and development model. During the trial, data were collected using a questionnaire (Likert Scale). This study's population was the eighth-grade students, which comprised six classes at SMP Negeri 35 Pekanbaru in semester one of the 2022/2023 school year. In this investigation, one class of 30 samples was used to determine the sample. The findings of the superficial module expert's assessment of the feasibility of printed modules based on crosswords attained a percentage score of 96.875% with a very valid category. The results of the educator's reaction to the print module achieved a percentage score of 93.75% with a fascinating category, and the results of the student response achieved a percentage score of 87.75% with a very interesting category, implying that product development was practicable to use.ABSTRAK: Penelitian ini bertujuan untuk mengembangkan bahan ajar berupa modul cetak IPA untuk bahan struktur jaringan tanaman dan penggunaannya dalam teknologi berbasis teka-teki silang kelas VIII. Jenis penelitian yang dilakukan adalah penelitian dan pengembangan model ADDIE. Data dikumpulkan melalui kuesioner (Skala Likert) pada saat persidangan. Populasi dalam penelitian ini adalah VIII yang terdiri dari 6 kelas di SMP Negeri 35 Pekanbaru pada semester 1 tahun ajaran 2022/2023. Untuk menentukan sampel dalam penelitian ini berjumlah 1 kelas yang terdiri dari 30 sampel. Hasil penilaian ahli modul superfisial terhadap kelayakan bahan ajar berupa modul cetak berdasarkan teka-teki silang mencapai skor persentase 96,875 % dengan kategori sangat valid. Hasil respon pendidik terhadap modul cetak mencapai skor persentase 93,75 % dengan kategori sangat menarik dan hasil respon siswa mencapai skor persentase 87,75% dengan kategori sangat berminat, sehingga disimpulkan produk pengembangan layak digunakan.